Interstitial deletion of the short arm of chromosome 4. Issue 3 (June 1984) - Ray, M; Evans, J; Rockman-Greenberg, C; Wickstrom, D
Abstract : A 17 year old girl investigated for mental retardation and minor anomalies was found to have an interstitial deletion of 4p. Her clinical and cytogenetic findings are compared with previous reported case of interstitial 4p deletion and with terminal 4p--deletions (Wolf-Hirschhorn syndrome).